KECANTIKAN WANITA KOREA SEBAGAI KONSEP KECANTIKAN IDEAL DALAM IKLAN NEW POND’S WHITE BEAUTY: WHAT OUR BRAND AMBASSADORS ARE SAYING - Arsitowati, Winta Hari (Faculty of Humanities, Diponegoro University, 2017)
This study aims to reveal the discourse contained in the advertisement of New POND'S White Beauty: What Our Brand Ambassadors are Saying and its relation to the life of the people in Southeast Asia. The researcher uses the critical discourse analysis method by Norman Fairclough to examine the advertisement which portrays the brand ambassadors from Indonesia, the Philippines and Vietnam's assesments about POND'S White Beauty product which is claimed to make their skin as white as Korean women. The researcher focused on the text analysis and social praxis based on the content of the advertisement. The researcher also adopted Poscolonial approach, focusing on the use of mimicry theory by Homi K. Bhabha after knowing the link between the text in the advertisement and the social praxis. By using mimicry theory, the researcher is able to know the perception of women in Southeast Asia, especially Indonesia, about Korean women who have smooth and white skin. The researcher finds that the New POND'S White Beauty: What Our Brand Ambassadors are Saying advertisement shows the discourse of Korean women's beauty skin as the new ideal standard of beauty which believed by Southeast Asian. It is represented by the three brand ambassadors in the advertisement. Thus, it can be said that South Korea as one country in Asia has the power to spread its culture and colonize other countries there. It also shows that colonization of Asian countries is no longer only done by Western countries, but also by the fellow Asian countries themselves.